2020
DOI: 10.24953/turkjped.2020.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Peters Plus syndrome: a recognizable clinical entity

Abstract: Peters plus syndrome is a rare genetic condition wherein multiple systemic involvement with distinctive facial features are manifested, whilst the hallmark is Peters anomaly, occuring from anterior segment dysgenesis. Homozygous variants in the B3GLCT gene were identified to underlie this disorder. We here report on a onemonth-old female patient with typical features characteristic of Peters plus syndrome in whom a homozygous pathogenic mutation in the B3GLCT gene was detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
0
13
0
3
Order By: Relevance
“…The B3GLCT gene variants causes Peters plus syndrome which is characterized by eye abnormalities, short stature, intellectual disability, ventriculomegaly and distinctive facies 16 . This case had compound heterozygous, autosomal recessive inheritance and the family had terminated a prior pregnancy due to ventriculomegaly.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The B3GLCT gene variants causes Peters plus syndrome which is characterized by eye abnormalities, short stature, intellectual disability, ventriculomegaly and distinctive facies 16 . This case had compound heterozygous, autosomal recessive inheritance and the family had terminated a prior pregnancy due to ventriculomegaly.…”
Section: Resultsmentioning
confidence: 97%
“…In the original PAGE study this was initially reported as 'potentially clinically relevant' because the contribution to the phenotype which commonly includes choanal atresia, malformations of the heart, inner ear and retina, 15 The B3GLCT gene variants causes Peters plus syndrome which is characterized by eye abnormalities, short stature, intellectual disability, ventriculomegaly and distinctive facies. 16 This case had compound heterozygous, autosomal recessive inheritance and the family had terminated a prior pregnancy due to ventriculomegaly.…”
Section: Fetuses With An Isolated Single Cns Anomalymentioning
confidence: 96%
“…The association of Peter's anomaly along with short stature, rhizomelia, broad short hands or brachydactyly, with facial dysmorphism, cleft lip, cleft palate, genitourinary and cardiovascular anomalies is a distinct and is often termed Peter's plus syndrome 10,11 . Here, the condition is often autosomal recessive due to homozygous mutations in B3GLCT 10–12 . This results in loss of glycosylation of the beta 1,3 glucosyltransferase enzyme 13 …”
Section: History and Physicalmentioning
confidence: 99%
“…In Peter's anomaly, this separation does not happen and this results in the corneal opacification and variable degree of irido‐corneal and corneolenticular adhesions. Mutations in the B3GLCT ( B3GALTL ) gene on chromosome 13q12.3 have been identified with Peter's plus anomaly 9–12 …”
Section: Aetiologymentioning
confidence: 99%
See 1 more Smart Citation